D. José Gomes, a revolução pela palavra dos planos de pastorais às CEBS (1966-1976) - Gomes, Paulo de Oliveira (2019)
Firstly the research discusses the Protagonism of the Diocesan Bishop from Chapecó Dom José Gomes, for the emergence by social leaders in the west region of Santa Catarina. Dom José assumed the Church of the West Santa Catarina in 1968, after actively participating in the Second Vatican Council sharing ideas and ideals of freedom theology and Catholic leaders who influenced the thinking Catholic Church in Brazil to choose the poor. Then the consolidation Monsignor José Gomes's proposal, the formation of popular leadership from biblical circles, reflection groups, the opening of the church to the leadership of lay leaders, began to work in oder to transformation Western history, with the the emergence of the Basic Ecclesial Communities (BECs) and social movements. So this dissertation searched in the archives of the Diocesan Miter documents contained in Dom José's personal folders, letters, agendas, manuscripts, notebooks and the Pastoral Plans with observations, directions, determinations, notes of the bishop. The Diocesan Miter archives contain a documentary collection still to be explored. This research sought to understand the influence of Bishop Dom José Gomes's thinking, the role of the BECs in the Diocese of Chapecó, the ecclesiological formation by Dom José and a reflection on Bishop's vision in the Roman Catholic Church. Moreover the process formation on BECs, we find the numerous pastoral plans that guided the action of the church, the emergence Bible schools and reflection groups, culminating with the base ecclesial communities in the diocese. The path taken to empower simple people who have become leaders of social movements and the Church. Finaly the documents which we had access to the Diocesan Mitra archives portray the accounts of all social segments about the importance of Dom José Gomes's contributions to the history at West Santa Catarina. They are testimonies of personality, actions, ideas and repercussions that even today, his words provoke in the process of community organization at Diocese of Chapecó and even beyond its borders. Dom José's words made the leaders reflect and dream, urged them to seek some utopia and gave direction, the way forward in the pursuit of quality of life.